PERAN KOMUNITAS BELAJAR PADA RELATIONSHIP MANAGEMENT GURU SEKOLAH DASAR DI GUGUS 21 SUNGAI RINGIN - Tuponawati, Safitri (Jurnal Visi Ilmu Pendidikan, 2026)
Abstract This study aims to analyze the relationship management of elementary school teachers and the role of professional learning communities in improving it. The research was conducted in Cluster 21 Sungai Ringin, Sekadau Hilir District, focusing on the learning communities at SD Negeri 47 Penanjung and SD Negeri 17 Mungguk. Using a descriptive qualitative approach, data were collected through semi-structured interviews, participant observation, and document studies involving 16 participants (principals, teachers, parents, and students). The results reveal that teacher relationship management underwent a transformation from formal, individual, and reactive patterns to more collaborative, empathetic, and proactive approaches. This change includes improved two-way communication with students, solid teamwork among teachers, and closer partnerships with parents. The learning community proved to be a crucial catalyst through its five main functions: (1) a safe space for reflection and sharing experiences; (2) a facilitator of contextual professional development; (3) a strengthener of collaboration and solidarity among teachers; (4) an accelerator for curriculum adaptation; and (5) a bridge to parents. This study concludes that a structured and committed learning community is an effective strategy for developing teacher relationship management in a resource-limited context, ultimately creating a healthier and more supportive learning ecosystem at the elementary school level. Keywords: Learning Community, Relationship Management, Elementary School Teacher, Collaboration, Educational Communication. Abstrak Penelitian ini bertujuan untuk menganalisis relationship management guru sekolah dasar dan peran komunitas belajar dalam meningkatkannya. Studi dilaksanakan di Gugus 21 Sungai Ringin, Kecamatan Sekadau Hilir, dengan fokus pada komunitas belajar di SD Negeri 47 Penanjung dan SD Negeri 17 Mungguk. Menggunakan pendekatan kualitatif deskriptif, data dikumpulkan melalui wawancara semi-terstruktur, observasi partisipan, dan studi dokumen yang melibatkan 16 partisipan (kepala sekolah, guru, orang tua, dan siswa). Hasil penelitian mengungkap bahwa relationship management guru mengalami transformasi dari pola yang bersifat formal, individual, dan reaktif menjadi lebih kolaboratif, empatik, dan proaktif. Perubahan ini mencakup peningkatan komunikasi dua arah dengan siswa, kerja tim yang solid antar guru, serta kemitraan yang lebih erat dengan orang tua. Komunitas belajar terbukti berperan sebagai katalis krusial melalui lima fungsi utamanya: (1) ruang aman untuk refleksi dan berbagi pengalaman; (2) fasilitator pengembangan profesional yang kontekstual; (3) penguat kolaborasi dan solidaritas antar guru; (4) akselerator adaptasi kurikulum; serta (5) jembatan penghubung dengan orang tua. Penelitian ini menyimpulkan bahwa komunitas belajar yang terstruktur dan berkomitmen merupakan strategi efektif untuk mengembangkan relationship management guru dalam konteks sumber daya terbatas, yang pada akhirnya menciptakan ekosistem belajar yang lebih sehat dan suportif di tingkat sekolah dasar.